Auricular Intradermal Acupuncture as a Supplementary Motor Rehabilitation Strategy in Poststroke Patients: A Randomized Preliminary Clinical Study. (19th March 2020) - Miao, Dan; Lei, Kuok-Tong; Jiang, Jing-Feng; Wang, Xin-Jun; Wang, Hong; Liu, Xiao-Ru; Zhang, Jia-Jia; Xiong, Jia-Wei
Abstract : We have explored the potential of auricular intradermal acupuncture (AIA) in standard rehabilitation and acupuncture treatment for motor recovery in poststroke patients. This was a randomized, controlled preliminary clinical study in which the patients were randomly assigned to the CT group (conventional treatment, standard rehabilitation, and routine acupuncture) or AIA group (AIA combined with conventional treatment) and underwent 6 sessions in 1 week (6 days). Standard procedures and previously reported acupuncture points were used. Clinical outcomes were measured by the Fugl-Meyer motor assessment (FMA) of flexor and extensor synergy movement (FSM and ESM) of the upper and lower extremities (UE and LE) at days 0, 3, and 6. The assessment was performed by blinded assessors. The AIA group showed a significant increase in FMA-UE/FMA-LE scores on day 3 (P = 0.012 and 0.001, respectively) and day 6 (P = 0.041 and P < 0.001, respectively), but this was not observed in the CT group. Furthermore, unlike the CT group, the AIA group exhibited a significant increase in the FMA-LE score on day 3 (P = 0.004 ) and the FMA-UE scores on day 6 (P = 0.048 ). Finally, the correlation between ESM and FMA-UE/FMA-LE was higher than that between FSM and FMA-UE/FMA-LE after treatment: for ESM and UE, r  = 0.759, P = 0.007 ; for ESM and LE, r  = 0.697, P = 0.003 ; for FSM and UE, r  = 0.604, P = 0.049 ; for FSM and LE, r  = 0.347, P = 0.188 . AIA is useful for motor rehabilitation in poststroke patients, particularly in terms of improving extensor synergy. This trial is registered with CHiCTR1800020150 .